PROGRAMA DE FORMAÇÃO CONTINUADA DE PROFESSORES DO ESTADO DO PARANÁ NA MODALIDADE DE SEMANAS PEDAGÓGICAS 2007-2014: UMA ANÁLISE A PARTIR DA AVALIAÇÃO DOS PEDAGOGOS - Justus, Michélle Barreto (2015)
This paper presents an analysis of the continuing education program of the State of Paraná teachers, in the modality of Pedagogical Weeks 2007-2014, based on the evaluation of pedagogues. The research goal was to analyze the teacher training program in the modality of Pedagogical Weeks developed in public schools of Ponta Grossa in the period, with the guiding question: what is the assessment of public schools' pedagogues on the continuing education program of teachers, proposed by the SEED-PR, in the modality of Pedagogical weeks, from 2007 to 2014? The research field were state schools of a Paraná county, and the subjects participants were pedagogues teachers who work in the state system for at least 7 years, which were selected by sampling proportional to the size of the schools. The specific objectives were: a) to characterize the continuing education program for teachers proposed by SEED / PR for the public schools of Paraná; b) to investigate the meanings of the assessment of the continuing education program for teachers assigned by the pedagogues of public schools of Ponta Grossa; c) to discuss the potentialities and weaknesses of Pedagogical Weeks of continuing education program of evidenced teachers on the results of the evaluation process carried out with the schools pedagogues and d) to point out the contributions, perspectives and challenges for the development of a continuing education program for teachers aiming the improvement of continuous training and education of the state's public schools. The research was conducted in a qualitative approach, a case study evaluation was lead, and the procedures used were documental analysis and questionnaire consisting of open and closed questions. The questions were tabulated, categorized and analyzed, considering the dimensions: relevance of the themes, adequacy of available materials, SEED's methodological guidelines to carry out the activities, the development of the proposed activities within the school and the contributions of the studies for the teaching and pedagogical work. The theoretical framework was built in dialogue with leading authors about the epistemological assumptions of educational assessment and evaluation of policies and programs, such as Afonso (2009; 2010; 2011), Guba and Lincoln (2011), Draibe (2001), Belloni (2001 ), Ferreira and Tenório (2010) and Fernandes (2011); and Nóvoa authors (2002), Tardif (2002) and Araujo;Araújo and Silva (2015) about the fundamentals of the continuing education of teachers, among others. The research results indicate that there were different conceptions of continuing education in both evaluated periods, in other words, in the development of pedagogical weeks in the governments of Roberto Requião (2007-2010) and Beto Richa (2011-2014), which expresses the assumptions on which the policies for education setled in Paraná in the period they ruled. Pedagogical weeks in the period 2007-2010 were best evaluated by pedagogues than in 2011-2014. The weaknesses observed in this study indicate the need to achieve more significant levels of efficiency, efficacy and institutional and social effectiveness, which suggests some adjustments to the development of this modality of continuing education for teachers in public schools of Paraná.